Implications of Population Growth on the Quality of Life of City Dwellers in Enugu State, Nigeria - Onah, Vincent C. (University of Nigeria Journal of Political Economy, 2022)
Nigeria remains the most populous country in Africa and the seventh globally. The country has estimated population of 198 million. The recent World Population Prospect predicts that by 2050, Nigeria will become the third most populated country in the world. The country’s average annual population growth rate is 6.5 per cent without commensurate increase in social amenities. Currently, Nigerian cities host wide spread poverty, under-employment, unemployment and insecurity. Ideally it is the duty of the state to regulate population growth in accord with economic development. In most post-colonial formations like Nigeria, policies made to regulate population growth have not been successful in terms of moderating the population growth vis-à-vis economic growth. Thus, the Act of the National Assembly which made it legal for a married woman to procreate 4 children only was defeated by the culture and religion of the people. This article investigated the incidence of population explosion in Nigeria and its implication on the quality of life of the city dwellers in 2019 and beyond. Specifically, the research investigated the causes and consequences of population growth in Nigeria. The study is a qualitative research and it relied on the Marxist theory of the post-colonial state. It found that the culture and religion of the people has rekindled the population increase in Nigeria. Consequently, the paper made cogent recommendations on the ways to bridge the gap between population explosion and economic growth.